In Vitro Fertility of Post-thawed Epididymal Ram Spermatozoa after Storage at 5 °C before Cryopreservation - N W.K Karja; M fahrudin; M A Setiadi (Media Peternakan, 2013)
This study addressed the effects of storage duration of epididymides at 5 °C before sperm collection and their fertility after cryopreservation in vitro. Spermatozoa from one of the testes pairs were immediately collected, evaluated and frozen (control group). The remaining epididymides were cooled to 5 °C and stored for 24, 48, 72, and 96 h (experimental groups), after which spermatozoa were collected and frozen as in the control group. Before and after thawing, sperm motility, sperm viability and plasma membrane integrity were assessed. The fertilizing ability of frozen-thawed spermatozoa of each group was evaluated by in vitro fertilization of matured sheep oocytes. Sperm quality (sperm motility, viability, and plasma membrane integrity) at collection and after cryopreservation decreased as the duration of the epididymal storage interval increase (P < 0.05). The motility decreased steadily along the studied time periods. Although, the fertilizing ability of post-thawed epididymal spermatozoa gradually decreased as the storage period was prolonged, the spermatozoa collected from the cauda epididymides stored at 5 °C for up to 96 h were able to fertilize 16%-65% of oocytes in vitro. Results of the present study showed that ram epididymal spermatozoa survive in storage at 5 °C for up to 96 h. These spermatozoa maintain their fertilizing ability and may be suitable for use in IVF and other assisted reproductive procedures.